Paranormal experience and survival of death - Becker, Carl B., 1951- (Albany : State University of New York Press, 1993)
This text amasses data and surveys from a century of research on the paranormal on four continents: Europe, Asia, and the Americas. Studying the tensions between religious and scientific perspectives, the author reviews numerous substantiated accounts of demon-possession, of memories of past lives, of ghostly apparitions, and out-of-body experiences. He analyzes the medical evidence and what such experiences imply about survival after death. The author then looks at the reasons for the taboos on scientific discussion of such research within the social sciences, and proposes a new paradigm for a more holistic view of the field.
Proof of reincarnation? -- Invisible bodies? -- The heart of near-death experiences -- Philosophy of science -- A model of resistance and change in the sciences -- What will the next world be like?
Includes bibliographical references (pages 219-249) and index.
Print version record.
JSTOR
Keywords: Future life; Spiritualism; Parapsychology and science; Spiritualism; Vie future; Spiritisme; Parapsychologie et sciences; spiritualism; BODY, MIND & SPIRIT -- Parapsychology -- Near-Death Experience; Future life; Parapsychology and science; Spiritualism; Psiphänomen; Nahtoderfahrung; Dood; Bijna-dood-ervaringen.; Spiritualisme